DIGITAL DA'WAH AND THE RECONSTRUCTION OF ISLAMIC AUTHORITY - A’lan Tabaika, Mokhammad; Barizi, Ahmad; Arif, Yunifa Miftachul (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2025)
This study addresses the research gap regarding how Islamic authority is contested and reconstructed in the era of digital media, where social media dynamics disrupt traditional hierarchies. It aims to analyze how online Islamic preaching is transformed by social media logics, aesthetic strategies, and audience engagement, emphasizing the participatory and dialogical nature of comment sections. This research adopts a qualitative design using a netnographic approach, observing and analyzing social media content produced by prominent Indonesian Islamic figures, including Hanan Attaki, Abdul Somad, and Habib Husein Ja’far. The dataset comprises YouTube sermons, Instagram posts, TikTok videos, and user interactions, including comments and shares. Findings reveal the emergence of